Dietary vitamin B12 deficiency in an adolescent white boy. Issue 6 (1st June 2002) - O'Gorman, P; Holmes, D; Ramanan, A V; Bose-Haider, B; Lewis, M J; Will, A
Abstract : Dietary deficiency of cobalamin resulting in tissue deficiency in white individuals is unusual. However, several patients with dietary deficiency who were neither vegan nor Hindu have been described. This report describes the case of a 14 year old boy who was a white non-Hindu with a very low intake of cobalamin, which was not apparent until a detailed dietary assessment was performed. The patient responded rapidly to a combination of oral and parenteral B12. This case illustrates the fact that severe dietary vitamin B12 deficiency can occur in non-Hindu white individuals. Inadequate dietary content of B12 may not be apparent until a detailed dietary assessment is performed. This patient is likely to have had subclinical vitamin B12 deficiency for several years. Increased vitamin B12 requirements associated with the adolescent growth spurt may have provoked overt tissue deficiency.